Analisis Permintaan Tenaga Kerja pada Industri Kecil dan Mikro di Indonesia Tahun 2018-2021 - Yesi Krismunita Dewi; Edy Yusuf Agung Gunanto (Universitas Diponegoro, 2023)
This research aims to analyze labor demand in small and micro industries in Indonesia from 2018 to 2021. A stationarity test was conducted first to determine the appropriate method for the time series data. The method used in this study is panel data regression, which combines time series data (2018-2021) and cross-sectional data (23 industrial subsectors according to the Indonesian Standard Classification of Business Fields) with a fixed effects model (FEM). The results indicate that output has a positive effect on labor demand, while wages and the dummy variable for goods industries do not significantly affect labor demand in small and micro industries in Indonesia.